DEVELOPING DELAY JITTER, THROUGHPUT, AND PACKAGE LOST: IPERF3 for Learning Islamic Education - Agusriandi Agusriandi; Elihami Elihami (Fakultas Teknik Universitas Muhammadiyah Parepare kerjasama P3M STKIP Muhammadiyah Enrekang, 2020)
Many providers offer the best Quality of Service. However, the offer is not always true in fact. Therefore, the purpose of this research is to know: (i) variation of delay that occurs, whether the greater the load of traffic provided will also affect the quality of jitter. (ii) the reliability of the packet to the destination (throughput) (iii) how reliable the technology is used in maintaining a packet for forwarding to investigate for learning Islamic Education by using mobile. The method used is to communicate directly with iperf.he.net server (216.218.227.10) for 30 seconds using some background traffic using iperf3 application. The experimental results are averaged and analyzed by comparing QoS of Jitter, Throughput, and Packet loss. From the experiment results it is known that scenario 2 (provider telkomsel) is the least delay and most stable according to TIPHON standard for learning Islamic Education by using mobile.